Information Entropy in Translation: Psycholinguistic Aspects - Дорофеєва, Маргарита; Андрущенко, Тетяна (Psiholìngvìstika, 2019)
The article deals with the category of informational entropy in the source text as a matter of translation psycholinguistics. The informational entropy of the lexical units on different levels in the source text refers to subjective factors that reduce the translation quality. Lexical units-carriers of the source text’s informational entropy cause informational deficits in the translator’s consciousness. The aim of the search is to consider the category of informational entropy from the standpoint of psycholinguistics and cognitive translation theory, identify the causes of informational entropy, establish linguistic and genre-stylistic markers of the lexical entropy units in the source text, identify ways to minimize entropy in the specialized translation. The research procedure involves a psycholinguistic experiment with the participation of 85 informants with semi-professional translation status. The participants produced a German-Ukrainian translation of a specialized text, in which the number of lexical units contained informational entropy as a percentage of the total words’ number was 17.9%. The results of the translation’s comparative analysis indicate similar psycholinguistic mechanisms for understanding lexical units with informational entropy, leading to false translation solutions in the target texts. Such mechanisms include an incorrect choice of the translation method and a lack of attention to the extralinguistic information in the source text. The conclusions of the psycholinguistic experiment confirm the universal nature of the informational entropy, resulting in translation quality degradation. The psycholinguistic factor for the false translation solutions is an automatic suppression the contextual meaning of the source text’s lexical item by its subject-logical meaning in the translator’s mind, realized in the incorrect choice of the translation method.